Tracing Virtual Sápmi: Communicating Sámi Narratives in the Age of the Meme - Lahey-McCoy, Faith (UiT Norges arktiske universitet, 2022)
Online social realities now more integrated into the daily lives of global human populations than has ever been witnessed before leads us to question how this shift might be impacting existing local realities. One phenomenon which characterizes today’s online interactions is the creation and sharing of internet memes, or images from pop culture often layered with text to convey ideas and perspectives through the vehicle of humour. In this thesis I explore Sámi memes and Sámi memeing culture on Instagram, a popular social media site, to better understand how the online Sámi community is using this medium to communicate Sámi narratives. While similarly, I attempt to demonstrate how these narratives becoming magnified in virtual spaces and how this might apply to the theory of a cultural interface. In doing so, I also aim to uncover the multifaceted nature of Sámi memes and how they contribute to discourses of decolonization, intersectionality, and indigenization. In centring their own knowledges to communicate community needs and expectations, using mainly empirical data grounded in an Indigenous online research methodology, it is through the lenses of three Sámi online meme creators that I contextualize the nature of contemporary Sámi realities. Furthermore, in exploring themes of Sámi language reclamation and revitalization, humour, and Indigenous cyberactivism through a Sámi memeing culture, I present the notion of citizenship as it might apply to the concept of a ‘Virtual Sápmi’.